Digitally mediated eating: Understanding the transformation of contemporary food lifestyles - Xin-Jean Lim; Joya A. Kemper; C. Michael Hall; Isaac Cheah (Appetite, 2026)

Land use legacies shape wild boar (Sus scrofa) diet along a forest-urban gradient in Singapore - Jasmine J. M. Ong; Max D. Y. Khoo; Li Si Tay; Bryan T. M. Lim; Charles J. Marsh; Melvyn Aik San Tan; Wen Xuan Chiok; G. Kenny Png; Matti A. Niissalo; Gillian S. W. Khew; Marcus A. H. Chua; Malcolm C. K. Soh; et al. (Urban Ecosystems, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Utilizing tropical tree rings to trace the spatial and temporal distribution of mercury levels in Cebu, Philippines - Cristi Cesar F. Megraso; Krizella Rhea T. Batulan; Janelle C. Lauron; Jon David C. Suico; A. J. Kenneth P. Sumagang; Jill R. Quitayen; Patrick John Y. Lim (Environmental Science and Pollution Research, 2026)

Membrane technologies for the removal of micro- and nanoplastics: Mechanisms, challenges and future directions - En Qi Lim; Hong Heng See; Woei Jye Lau; Pei Sean Goh; Michael C. Breadmore; Ahmad Fauzi Ismail (Journal of Environmental Chemical Engineering, 2026)

Revisiting tandem duplication in plant genomes: Technical challenges and pangenome solutions - Sung Don Lim; John C. Cushman; Won Cheol Yim (Current Opinion in Plant Biology, 2026)

Evaluation for the machine learning based PM2.5 estimation using different spatial resolution of geostationary satellite AOD over megacities in Korea - Juhee Lee; Jhoon Kim; Yeseul Cho; Seoyoung Lee; Drew C. Pendergrass; Daniel J. Jacob; Hyunkwang Lim; Hahn Chul Jung; Kwang-Min Myung; Young-Doh Kim; Kyung Man Han; Ja-Ho Koo (Atmospheric Environment, 2026)

Littered cigarette butts in urban streets in Southern Philippines - K. N. D. Araña; Y. C. Lim; F. P. J. B. Albarico; A. A. Aguilar; H. D. Maruhom; J. I. D. S. Ungang; N. G. Dimaongon; C.-W. Chen; C.-D. Dong; H. P. Bacosa (International Journal of Environmental Science and Technology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Coronary CT Angiography-Based Prediction Model for Hemodynamically Significant Coronary Stenosis Integrating Morphological and Plaque Characteristics - Chenxi Wang; Shuang Leng; Ru-San Tan; Ping Chai; Jiang Ming Fam; Adrian Fatt Hoe Low; Lohendran Baskaran; Lynette Teo; Felix Yung Jih Keng; Chee Yang Chin; Ching Ching Ong; John C. Allen; et al. (Cardiovascular Engineering and Technology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Potential ecological risk due to chromium and lead contamination in the sanitary landfill of Cebu City, Philippines: implications for site rehabilitation and restoration for development - Mary Jasmelle D. Camañan; Dara Faye T. Daguison; Nikki Marie O. Marquez; Christine C. Velarde; Danilo T. Dy; Patrick John Y. Lim (Environmental Science and Pollution Research, 2026)

Expert perspectives on exposure-response functions for urban health policy: Lessons from a UBDPolicy workshop - Harry Williams; Zorana Jovanovic Andersen; Hanna Boogaard; Søren Brage; Matthew H.E.M. Browning; Samuel Cai; Xuan Chen; Priyanka deSouza; Angel M. Dzhambov; Benjamin Fenech; Gillian Flower; Francesco Forastiere; et al. (Environmental Research, 2026)

Cyclic moisture reactivation of calcium sorbents for long duration thermochemical energy storage - Lyu Zhou; Sankeerthana Manchikatla; Diwash Dhakal; Madeline Van Winkle; Michael Adams; Ju won Lim; Malitha C. Dickwella Widanage; Roma Avhad; Katherine Jungjohann; John S. Mangum; Akanksha K. Menon; Shannon Yee; et al. (Chemical Engineering Journal, 2026)

Systems-Level Phosphoproteomic and RPPA Profiling Reveals Stress and DNA Damage Signalling as Early Drivers of Polymyxin B Neurotoxicity - Maytham Hussein; Thuraya Safaa Ansaf; Terry C. C. Lim Kam Sian; Mark Baker; Pouya Faridi; Zhi Ying Kho; Nivedhitha Selvakumar; Keith S. Kaye; Gauri G. Rao; Jian Li; Tony Velkov (Molecular Neurobiology, 2026)
Polymyxins remain indispensable last-line antibiotics for multidrug-resistant Gram-negative infections, yet their clinical use in central nervous system (CNS) infections is constrained by poorly understood neurotoxicity. Here, we define the early molecular signalling events underlying polymyxin B-induced CNS toxicity using an integrated phosphoproteomic and Reverse Phase Protein Array (RPPA) approach in rat brain following intracerebroventricular administration. Global phosphoproteomics revealed extensive phosphosite coverage but identified a highly selective set of significantly regulated phosphosites, implicating calcium-dependent signalling, transcriptional stress regulation, synaptic signalling, and cytoskeletal control, while parallel total proteomics showed minimal changes in protein abundance. RPPA profiling independently confirmed coordinated modulation of stress, apoptotic and survival-associated signalling pathways, including p53, CREB, SQSTM1, Bcl-2, and NFκB related nodes. Network and functional enrichment analyses converged on DNA damage signalling, apoptotic regulation and growth factor-mediated pathways as central features of the polymyxin B early neurotoxicity response, while phosphor to total protein analyses demonstrated suppression of proliferative and pro-survival signalling. Together, these data establish phosphorylation-driven signalling reprogramming as a primary early mechanism of polymyxin B-induced neurotoxicity, providing a mechanistic framework that links membrane-active antibiotic exposure to neuronal stress signalling and identifies candidate pathways for toxicity biomarkers and neuroprotective strategies.

Notes on the Sexual Reproduction of Selected Broadcast Spawning Corals in Cebu, Central Philippines - Katrene C. Cerna; Ma. Katrina Lanaria-Lim; Antonio N. Ayop; Emmeline A. Jamodiong; Kurt Bryant B. Bacharo; Ronald D. Villanueva; Patrick C. Cabaitan; Anthony S. Ilano (Thalassas: An International Journal of Marine Sciences, 2025)

Developing Joule-heating regeneration of carbon-based adsorbents for Direct Air Capture - Kepler Petzall; Benjamin J. Rhodes; Yongqiang Wang; Teedhat Trisukhon; Hari Kukreja; S. Alexandra Lim; Phillip J. Milner; Alexander C. Forse (Chemical Engineering Journal, 2025)

Rapid and precise method for microplastic analysis in Malaysian bottled water - En Qi Lim; Hong Heng See; Woei Jye Lau; Pei Sean Goh; Michael C. Breadmore; Haruka Takeuchi; Ahmad Fauzi Ismail (Journal of Environmental Chemical Engineering, 2025)

Thermodynamic and kinetic analysis of autothermal syngas-generating limestone calcination process for ammonia synthesis - Arian Ebneyamini; Zezhong John Li; Yeon Jae Lee; C. Jim Lim; Naoko Ellis; John R. Grace; Jun Young Kim (Fuel, 2025)

Molecular identification, carpospore development, and carrageenan characteristics of wild eucheumatoid Kappaphycopsis cottonii - Eka Sunarwidhi Prasedya; Hikmaturrohmi Hikmaturrohmi; Fildzah Zati Hulwani; Satya Reza Faturakhmat; Victor Nikijuluw; Shienna Mae C. Gonzaga; Lourie Ann R. Hinaloc; Phaik-Eem Lim; Michael Y. Roleda (Journal of Applied Phycology, 2025)

Empirical Geomorphic Approach to Complement Morphodynamic Modeling on Embayed Beaches - Changbin Lim; Jung-Lyul Lee; John R. C. Hsu (Journal of Marine Science and Engineering, 2025)
In a coastal engineering project, hydrodynamic models are used to study wave transformations and impacts on structures, while morphodynamic models are applied to calculate the response and evolution of sedimentary beaches. Conventionally, laboratory experiments and numerical modeling have been called to investigate beach changes, particularly those resulting in the formation of an embayed beach. The former is undertaken in a wave basin, necessitating a huge outdoor facility to fit a project with large dimensions, numerous instrumentations, and manpower, while the latter is performed by powerful numerical models on a desktop, requiring only the advent of computing power and professional skills. Conventionally, both approaches have successfully achieved the expected outcome, though differing in cost and time frame. On the contrary, an efficient empirical geomorphic model for headland-bay beaches has been available since 1989 for assessing the planform stability of a crenulated beach in static equilibrium. The model can readily produce a graphic display of the static bay shape aided by a supporting software within a shorter time frame (in a couple of minutes), instead of in hours or days in laboratory tests and numerical modeling. Several practical examples drawn by the software MeePaSoL for the empirical model are presented to complement the results of a morphodynamic model in a wave basin, as well as to guide the modeler to terminate the programming when equilibrium is reached. We believe this alternative approach could be helpful for the experimentalists and numerical modelers on large engineering projects associated with shoreline beach evolution and shore protection, especially for time-saving and reducing manpower and cost.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

In vitro cytotoxicity assessment of ruxolitinib on oligodendrocyte precursor cell and neural stem/progenitor cell populations - Cheng-Wei Lim; Gen Hamanaka; Anna C. Liang; Su Jing Chan; King-Hwa Ling; Eng H. Lo; Ken Arai; Pike See Cheah (NeuroToxicology, 2024)

Exploring synthesis techniques for an imidazole-based one-component epoxy latent curing agent: Chemical capping and mechano-chemical capsuling - Han Gyeol Jang; Deok Jae Lim; Sohyun An; Jong Hyuk Park; Min Park; Jinwoo Park; Hyungbum Park; Byeong-Su Kim; Doh C. Lee; Jaewoo Kim (Chemical Engineering Journal, 2024)

Wastewater and clinical surveillance of respiratory viral pathogens on a university campus - Steven C. Holland; Matthew F. Smith; LaRinda A. Holland; Rabia Maqsood; James C. Hu; Vel Murugan; Erin M. Driver; Rolf U. Halden; Efrem S. Lim (Science of The Total Environment, 2024)

P13-02 Polyhexamethylene guanidine phosphate induces lung fibrosis and cancer via the TAK1-related signaling pathway - H. Lee; S.H. Jeong; Y.-W. Baek; J.-H. Lee; C. Kim; H. Lee; J.K. Sa; J.Y. Lee; Y.-S. Lee; Y.J. Nam; J. Kim; J. Kim; et al. (Toxicology Letters, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Psychosocial barriers and facilitators for cascade genetic testing in hereditary breast and ovarian cancer: a scoping review - Agani Afaya; Sung-Won Kim; Hyung Seok Park; Myong Cheol Lim; Mi Sook Jung; Eun Ji Nam; Ji Soo Park; Joon Jeong; Jai Min Ryu; JiSun Kim; Jihye Kim; Minkyoung Kim; et al. (Familial Cancer, 2024)

Understanding diel bioaerosol patterns in mold-affected buildings through metagenomic surveillance - Irvan Luhung; Serene B.Y. Lim; Akira Uchida; Yee Hui Lim; Kenny J.X. Lau; Premkrishnan Balakrishnan; Stephan C. Schuster (Building and Environment, 2024)

Demonstrating the reliability of in vivo metabolomics based chemical grouping: towards best practice - Mark R. Viant; E. Amstalden; T. Athersuch; M. Bouhifd; S. Camuzeaux; D. M. Crizer; P. Driemert; T. Ebbels; D. Ekman; B. Flick; V. Giri; M. Gómez-Romero; et al. (Archives of Toxicology, 2024)
While grouping/read-across is widely used to fill data gaps, chemical registration dossiers are often rejected due to weak category justifications based on structural similarity only. Metabolomics provides a route to robust chemical categories via evidence of shared molecular effects across source and target substances. To gain international acceptance, this approach must demonstrate high reliability, and best-practice guidance is required. The MetAbolomics ring Trial for CHemical groupING (MATCHING), comprising six industrial, government and academic ring-trial partners, evaluated inter-laboratory reproducibility and worked towards best-practice. An independent team selected eight substances (WY-14643, 4-chloro-3-nitroaniline, 17α-methyl-testosterone, trenbolone, aniline, dichlorprop-p, 2-chloroaniline, fenofibrate); ring-trial partners were blinded to their identities and modes-of-action. Plasma samples were derived from 28-day rat tests (two doses per substance), aliquoted, and distributed to partners. Each partner applied their preferred liquid chromatography–mass spectrometry (LC–MS) metabolomics workflows to acquire, process, quality assess, statistically analyze and report their grouping results to the European Chemicals Agency, to ensure the blinding conditions of the ring trial. Five of six partners, whose metabolomics datasets passed quality control, correctly identified the grouping of eight test substances into three categories, for both male and female rats. Strikingly, this was achieved even though a range of metabolomics approaches were used. Through assessing intrastudy quality-control samples, the sixth partner observed high technical variation and was unable to group the substances. By comparing workflows, we conclude that some heterogeneity in metabolomics methods is not detrimental to consistent grouping, and that assessing data quality prior to grouping is essential. We recommend development of international guidance for quality-control acceptance criteria. This study demonstrates the reliability of metabolomics for chemical grouping and works towards best-practice.

Large language models for diabetes care: Potentials and prospects - Bin Sheng; Zhouyu Guan; Lee-Ling Lim; Zehua Jiang; Nestoras Mathioudakis; Jiajia Li; Ruhan Liu; Yuqian Bao; Yong Mong Bee; Ya-Xing Wang; Yingfeng Zheng; Gavin Siew Wei Tan; et al. (Science Bulletin, 2024)

Conspicuous, green flowers are an honest signal of nectar rewards in a bird-pollinated tree (Fuchsia excorticata, Onagraceae) - Ganges Lim; K. C. Burns (Plant Ecology, 2024)
Bird-pollinated flowers typically appear ‘red’. Fuchsia excorticata (Onagraceae), a gynodioecious tree species endemic to New Zealand, is a notable exception. It produces ‘green’, cauliflorous flowers at early stages in flower ontogeny, when pistils are receptive. Flowers later turn ‘red’ as they lose their receptivity. We conducted field observations and spectrographic analyses to test whether: (1) receptive, green-phase flowers are actually more conspicuous to avian pollinators against their natural backgrounds than unreceptive, red-phase flowers, (2) green-phase flowers produce more nectar, and (3) relationships between flower conspicuousness and nectar production are similar in females and hermaphrodites. Results showed that the reflectance properties of green-phase flowers sharply contrast ‘orange’ tree bark, their natural visual background, rendering them more conspicuous to the avian eye than red-phase flowers. Green-phase flowers also produced more nectar than red-phase flowers as an honest signal of rewards. Similar results were observed in both female and hermaphrodite plants. Overall results provide an unusual example of reversed flower-background colour contrasts, with ‘reddish’ hues being incorporated into the visual backgrounds of floral displays rather than being associated with the flowers themselves. They also illustrate that flower conspicuousness can serve as an honest signal of nectar rewards to pollinators.

Evaluating Bacillus flexus as bioremediators for ammonia removal in shrimp culture water and wastewater and characterizing microbial communities in shrimp pond sludge - M. Y. Jasmin; N. Mat Isa; M. S. Kamarudin; K. C. Lim; Murni Karim (Brazilian Journal of Microbiology, 2024)

Vasorelaxant effect of a phenylethylamine analogue based on schwarzinicine A an alkaloid isolated from the leaves of Ficus schwarzii - Kayatri Govindaraju; Yin Ying Mak; Fong Kai Lee; Claudia C. Bauer; Kuan Hon Lim; Robin S. Bon; Cin Kong; Sue Mian Then; Kang Nee Ting (Phytochemistry Letters, 2024)

Ecological network structure in response to community assembly processes over evolutionary time - Natalie R. Graham; Henrik Krehenwinkel; Jun Ying Lim; Phillip Staniczenko; Jackson Callaghan; Jeremy C. Andersen; Daniel S. Gruner; Rosemary G. Gillespie (Molecular Ecology, 2023)
The dynamic structure of ecological communities results from interactions among taxa that change with shifts in species composition in space and time. However, our ability to study the interplay of ecological and evolutionary processes on community assembly remains relatively unexplored due to the difficulty of measuring community structure over long temporal scales. Here, we made use of a geological chronosequence across the Hawaiian Islands, representing 50 years to 4.15 million years of ecosystem development, to sample 11 communities of arthropods and their associated plant taxa using semiquantitative DNA metabarcoding. We then examined how ecological communities changed with community age by calculating quantitative network statistics for bipartite networks of arthropod–plant associations. The average number of interactions per species (linkage density), ratio of plant to arthropod species (vulnerability) and uniformity of energy flow (interaction evenness) increased significantly in concert with community age. The index of specialization has a curvilinear relationship with community age. Our analyses suggest that younger communities are characterized by fewer but stronger interactions, while biotic associations become more even and diverse as communities mature. These shifts in structure became especially prominent on East Maui (~0.5 million years old) and older volcanos, after enough time had elapsed for adaptation and specialization to act on populations in situ. Such natural progression of specialization during community assembly is probably impeded by the rapid infiltration of non‐native species, with special risk to younger or more recently disturbed communities that are composed of fewer specialized relationships.

Total infectome investigation of diphtheritic stomatitis in yellow-eyed penguins (Megadyptes antipodes) reveals a novel and abundant megrivirus - Janelle R. Wierenga; Rebecca M. Grimwood; Harry S. Taylor; Stuart Hunter; Lisa S. Argilla; Trudi Webster; Lauren Lim; Rebecca French; Hendrik Schultz; Fátima Jorge; Mihnea Bostina; Laura Burga; et al. (Veterinary Microbiology, 2023)

Blazing a trail for the clinical use of rapamycin as a geroprotecTOR - Adam R. Konopka; Dudley W. Lamming; Brittany A. Grasso; Rebecca C. Marrah; Sara Decker; Neetika Garg; Yeonhee Park; Sin Yin Lim; Judith A. Simcox; Cara L. Green; Isaac Grunow; Amanjot K. Yadev; et al. (GeroScience, 2023)

Humboldt Review: Tissue succulence in plants: Carrying water for climate change - Arely V. Pérez-López; Sung Don Lim; John C. Cushman (Journal of Plant Physiology, 2023)

Nature-based solutions to manage particle-bound metals in urban stormwater runoff: current design practices and knowledge gaps - Kim N. Irvine; Lloyd H. C. Chua; Zhang Hua’an; Lim En Qi; Lim Yi Xuan (Journal of Soils and Sediments, 2023)

Comparison of different spatial temperature data sources and resolutions for use in understanding intra-urban heat variation - Ayda Kianmehr; Theodore C. Lim; Xiaojiang Li (Sustainable Cities and Society, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Dominant modes of precipitation over Africa, and their associated atmospheric circulations from observations - Kenny T. C. Lim Kam Sian; Alessandro Dosio; Brian O. Ayugi; Daniel F. T. Hagan; Laban L. Kebacho; Victor Ongoma (International Journal of Climatology, 2023)
This study uses the empirical orthogonal function (EOF) analysis to identify and describe continental‐scale seasonal (MAM, JJA, SON and DJF) precipitation modes over Africa based on observation (Global Precipitation Climatology Centre; GPCC) and reanalysis (ERA5) data from 1982 to 2014. Using composite analysis, we attempt to identify the atmospheric circulations (wind and relative humidity) associated with each precipitation mode. Precipitation from ERA5 has a good agreement with that of GPCC, as observed in the good spatial congruence in the EOF analysis and precipitation composites. The EOF results for each season show that the loading patterns of Mode 1 (variance >20% for all seasons) match the long‐term mean precipitation distribution. Atmospheric conditions across the continent are primarily driven by the four main high‐pressure systems (Azores, St. Helena, Arabian and Mascarene High) that influence moisture distribution and subsequently modulate the seasonal rain belt distribution. Modes 2 (variance >11% for all seasons) and 3 (variance >10% for all seasons) are deviations of the leading mode associated with smaller‐scale atmospheric systems. However, large‐scale factors still dominate the overall precipitation pattern by modulating the seasonal energy transfer between the hemispheres. The results provide a comprehensive understanding of the continental‐wide African seasonal precipitation modes and the associated atmospheric circulation from observations. The findings can be used as a reference for future work using model data for historical and projection studies.

Adsorption and electrochemical regeneration of 2D magnetic MXene nanosheets loaded with tetracycline - Ahsan Abdul Ghani; Bolam Kim; Mohsin Nawaz; Kamakshaiah C. Devarayapalli; Youngsu Lim; Gyuhyeon Kim; Dae Sung Lee (Chemical Engineering Journal, 2023)

Spatial distribution and baseline levels establishment of heavy metals in sediments along the Thai Binh coast, Vietnam - D. T. Lim; N. Q. Bac; D. N. Nhiem; D. D. Cham; N. T. L. Huong; N. T. Hue; N. T. H. Thuy; C. D. Duong; N. N. Pham; K.-U. Rudolph; J. Hilbig (International Journal of Environmental Science and Technology, 2023)

168 Low- and mid-level equine assisted services improved mood and state anxiety levels in health-care workers - K. Waite; C. Skelly; P. Hitzler; T. Guthrie; G. Shelle; S. Lim (Journal of Equine Veterinary Science, 2023)

Chromosome-length genome assemblies and cytogenomic analyses of pangolins reveal remarkable chromosome counts and plasticity - Marlys L. Houck; Klaus-Peter Koepfli; Taylor Hains; Ruqayya Khan; Suellen J. Charter; Julie A. Fronczek; Ann C. Misuraca; Sergei Kliver; Polina L. Perelman; Violetta Beklemisheva; Alexander Graphodatsky; Shu-Jin Luo; et al. (Chromosome Research, 2023)

Field factory for the automated harvesting of forestry tree stock - Benjamin J. McGuinness; Mike D. Duke; Kit C. Au; Hin S. Lim (Biosystems Engineering, 2023)

Comparative analysis of four types of mesoscale eddies in the North Pacific Subtropical Countercurrent region - part II seasonal variation - Wenjin Sun; Mengxuan An; Jishan Liu; Jie Liu; Jingsong Yang; Wei Tan; Kenny T. C. Lim Kam Sian; Jinlin Ji; Yu Liu; Changming Dong (Frontiers in Marine Science, 2023)
The North Pacific Subtropical Countercurrent area (STCC) is high in mesoscale eddy activities. According to the rotation direction of the eddy flow field and the sign of temperature anomaly within the eddy, they can be divided into four categories: cyclonic cold-core eddy (CCE), anticyclonic warm-core eddy (AWE), cyclonic warm-core eddy (CWE) and anticyclonic cold-core eddy (ACE). CCE and AWE are called normal eddies, and CWE and ACE are named abnormal eddies. Based on the OFES data and vector geometry automatic detection method, we find that at the sea surface, the maximum monthly number of the CCE, AWE, CWE, and ACE occurs in December (765.70 ± 52.05), January (688.20 ± 82.53), August (373.40 ± 43.09) and August (533.00 ± 56.92), respectively. The number of normal eddies is more in winter and spring, and less in summer and autumn, while abnormal eddies have the opposite distribution. The maximum rotation velocity of the four types of eddies appears in June (11.71 ± 0.75 cm/s), June (12.24 ± 0.86 cm/s), May (10.63 ± 0.99 cm/s) and June (9.97 ± 0.91 cm/s), which is fast in winter and spring. The moving speed of the four types of eddies is almost similar (about 10 ~ 11 cm/s). The amplitude of normal and abnormal eddies is both high in summer and autumn, and low in winter and spring, with larger amplitudes in normal than abnormal eddies. The eccentricity (defined as the eccentricity of the ellipse obtained by fitting the eddy boundary) of the four types of eddies is also close to each other, and their variation ranges from 0.7 to 0.8, with no apparent seasonal variation. The vertical penetration depth, which has no significant seasonal difference, is 675.13 ± 67.50 m in cyclonic eddies (CCE and CWE), which is deeper than that 622.32 ± 81.85 m in anticyclonic eddies (ACE and AWE). In addition, increasing the defined temperature threshold for abnormal eddies can significantly reduce their numbers but does not change their seasonal variation trend.

Maintenance of a fruit colour polymorphism along an elevational gradient in the Southern Alps of New Zealand - Ganges Lim; K. C. Burns (Oecologia, 2023)

Soil pollution driven by duration of urbanisation and dwelling quality in urban areas: An example from Auckland, New Zealand - A.P. Martin; C. Lim; M. Kah; M.S. Rattenbury; K.M. Rogers; E.L. Sharp; R.E. Turnbull (Applied Geochemistry, 2023)

Determinants of sun bear Helarctos malayanus habitat use in Sabah, Malaysian Borneo and its predicted distribution under future forest degradation and loss - Roshan Guharajan; Jesse F. Abrams; Nicola K. Abram; Hong Ye Lim; Gopalasamy Reuben Clements; Nicolas J. Deere; Matthew J. Struebig; Benoit Goossens; Penny C. Gardner; Jedediah F. Brodie; Alys Granados; Shu Woan Teoh; et al. (Biodiversity and Conservation, 2023)

Analysis and prediction of marine heatwaves in the Western North Pacific and Chinese coastal region - Yifei Yang; Wenjin Sun; Jingsong Yang; Kenny T. C. Lim Kam Sian; Jinlin Ji; Changming Dong (Frontiers in Marine Science, 2022)
Over the past decade, marine heatwaves (MHWs) research has been conducted in almost all of the world’s oceans, and their catastrophic effects on the marine environment have gradually been recognized. Using the second version of the Optimal Interpolated Sea Surface Temperature analysis data (OISSTV2) from 1982 to 2014, this study analyzes six MHWs characteristics in the Western North Pacific and Chinese Coastal region (WNPCC, 100°E ∼ 180°E, 0° ∼ 65°N). MHWs occur in most WNPCC areas, with an average frequency, duration, days, cumulative intensity, maximum intensity, and mean intensity of 1.95 ± 0.21 times/year, 11.38 ± 1.97 days, 22.06 ± 3.84 days, 18.06 ± 7.67 °Cdays, 1.84 ± 0.50°C, and 1.49 ± 0.42 °C, respectively, in the historical period (1982 ~ 2014). Comparing the historical simulation results of 19 models of the Coupled Model Intercomparison Project Phase 6 (CMIP6) with the OISSTV2 observations, five best-performing models (GFDL-CM4, GFDL-ESM4, AWI-CM-1-1-MR, EC-Earth3-Veg, and EC-Earth3) are selected for MHWs projection (2015 ~ 2100). The MHWs characteristics projections from these five models are analyzed in detail under the Shared Socio-economic Pathway (SSP) 1-2.6, 2-4.5 and 5-8.5 scenarios. The projected MHWs characteristics under SSP5-8.5 are more considerable than those under SSP1-2.6 and 2-4.5, except for the MHWs frequency. The MHWs cumulative intensity is 96.36 ± 56.30, 175.44 ± 92.62, and 385.22 ± 168.00 °Cdays under SSP1-2.6, 2-4.5 and 5-8.5 scenarios, respectively. This suggests that different emission scenarios have a crucial impact on MHW variations. Each MHWs characteristic has an obvious increasing trend except for the annual occurrences. The increase rate of MHWs cumulative intensity for these three scenarios is 1.02 ± 0.83, 3.83 ± 1.43, and 6.70 ± 2.61 °Cdays/year, respectively. The MHWs occurrence area in summer is slightly smaller than in winter, but the MHWs average intensity is stronger in summer than in winter.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Comparative analysis of four types of mesoscale eddies in the north pacific subtropical countercurrent region – part I spatial characteristics - Mengxuan An; Jie Liu; Jishan Liu; Wenjin Sun; Jingsong Yang; Wei Tan; Yu Liu; Kenny T. C. Lim Kam Sian; Jinlin Ji; Changming Dong (Frontiers in Marine Science, 2022)
The North Pacific Subtropical Countercurrent (STCC) region has high mesoscale eddy activities due to its complex circulation structure. This study divides these mesoscale eddies into four types: cyclonic cold-core eddy (CCE), anticyclonic warm-core eddy (AWE), cyclonic warm-core eddy (CWE), and anticyclonic cold-core eddy (ACE) according to the rotation direction of the eddy flow field and the sign of average temperature anomaly within the eddy after spatial high-pass filtering. CCE and ACE are called normal eddies, while CWE and ACE are named abnormal eddies. Using eddy-resolving model data (OFES), this work finds that the abnormal eddy phenomenon mainly occurs in the ocean’s upper layer. The eddy number proportion for CCEs, AWEs, CWEs, and ACEs at the sea surface is 35.60, 32.08, 12.95, and 19.37%. The corresponding average radius is 79.14 ± 3.7, 83.34 ± 3.75, 73.74 ± 4.14, and 79.46 ± 3.89 km, respectively. Each type of eddy’s average amplitude is about 3 cm. Regarding the eddy average eccentricity, the four types of eddies have very close eccentricities, with a range of 0.73 ~ 0.76. If the types of eddies are not distinguished, the eddies generated north of 21°N tend to move southward, while eddies generated south of that latitude tend to move northward. The depth of CCEs, AWEs, CWEs, and ACEs with average eddy nonlinearity larger than one is concentrated in the ocean’s upper layer at 109.0, 116.0, 159.0, and 52.0 m, respectively. This study deepens the understanding of the spatial distribution characteristics of mesoscale eddies in the STCC region.

Projected changes in meteorological drought over East Africa inferred from bias-adjusted CMIP6 models - Brian Ayugi; Zablon Weku Shilenje; Hassen Babaousmail; Kenny T. C. Lim Kam Sian; Richard Mumo; Victor Nnamdi Dike; Vedaste Iyakaremye; Abdelghani Chehbouni; Victor Ongoma (Natural Hazards, 2022)

Do fruit reflectance properties affect avian frugivory in New Zealand? - Ganges Lim; Kevin C. Burns (New Zealand Journal of Botany, 2022)
Fleshy fruits come in a diversity of colours. Some of this diversity can be attributed to unique selection pressures exerted by different types of frugivores. For example, mammals tend to consume green, yellow, orange and brown fruits, while birds normally consume red and black fruits. However, it is not yet clear whether the diversity of colours displayed within assemblages of bird‐dispersed fruits can be attributed to avian colour preferences. We tested whether the reflectance properties of a fleshy fruited plant community from New Zealand predict their removal by birds. All data were collected from 10 common fleshy‐fruited plant species during the austral summer (December 2018–April 2019) in a fenced forest reserve on the North Island of New Zealand. We found that fruit removal rates varied amongst plant species and frugivore preferences were not correlated with fruit conspicuousness, brightness, chroma and distinctiveness, suggesting that fruit reflectance properties are unrelated to avian frugivory in our study site. Overall, results from this study suggest that evidence for frugivore‐mediated selection of fruit colour diversity may be scale dependent and needs to be investigated at higher taxonomic scales. Future studies examining other factors such as fruit abundance and fruit displays may reveal the finer mechanisms of frugivore‐fruit selection

Projected changes in rainfall over Uganda based on CMIP6 models - Hamida Ngoma; Brian Ayugi; Charles Onyutha; Hassen Babaousmail; Kenny T. C. Lim Kam Sian; Vedaste Iyakaremye; Richard Mumo; Victor Ongoma (Theoretical and Applied Climatology, 2022)

A highly photoresponsive and efficient molybdenum-modified titanium dioxide photocatalyst for the degradation of methyl orange - D. Kanakaraju; M. A. A. Jasni; Y. C. Lim (International Journal of Environmental Science and Technology, 2022)

Persistent viral RNA shedding of SARS-CoV-2 is associated with delirium incidence and six-month mortality in hospitalized COVID-19 patients - Ayush Batra; Jeffrey R. Clark; Anthony K. Kang; Sareen Ali; Tulsi R. Patel; Nathan A. Shlobin; Steven C. Hoffman; Patrick H. Lim; Zachary S. Orban; Lavanya Visvabharathy; Edith L. Graham; David P. Sullivan; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Cycle Length Evaluation in Persistent Atrial Fibrillation Using Kernel Density Estimation to Identify Transient and Stable Rapid Atrial Activity - Szabolcs Z. Nagy; Patrick Kasi; Valtino X. Afonso; Nathaniel Bird; Brian Pederson; Ian E. Mann; Steven Kim; Nicholas W. F. Linton; David C. Lefroy; Zachary I. Whinnett; Fu Siong Ng; Michael Koa-Wing; et al. (Cardiovascular Engineering and Technology, 2022)
Purpose Left atrial (LA) rapid AF activity has been shown to co-localise with areas of successful atrial fibrillation termination by catheter ablation. We describe a technique that identifies rapid and regular activity. Methods Eight-second AF electrograms were recorded from LA regions during ablation for psAF. Local activation was annotated manually on bipolar signals and where these were of poor quality, we inspected unipolar signals. Dominant cycle length (DCL) was calculated from annotation pairs representing a single activation interval, using a probability density function (PDF) with kernel density estimation. Cumulative annotation duration compared to total segment length defined electrogram quality. DCL results were compared to dominant frequency (DF) and averaging. Results In total 507 8 s AF segments were analysed from 7 patients. Spearman’s correlation coefficient was 0.758 between independent annotators ( P < 0.001), 0.837–0.94 between 8 s and ≥ 4 s segments ( P < 0.001), 0.541 between DCL and DF ( P < 0.001), and 0.79 between DCL and averaging ( P < 0.001). Poorer segment organization gave greater errors between DCL and DF. Conclusion DCL identifies rapid atrial activity that may represent psAF drivers. This study uses DCL as a tool to evaluate the dynamic, patient specific properties of psAF by identifying rapid and regular activity. If automated, this technique could rapidly identify areas for ablation in psAF.

Chronic mild stress paradigm as a rat model of depression: facts, artifacts, and future perspectives - Tatyana Strekalova; Yanzhi Liu; Daniel Kiselev; Sharafuddin Khairuddin; Jennifer Lok Yu Chiu; Justin Lam; Ying-Shing Chan; Dmitrii Pavlov; Andrey Proshin; Klaus-Peter Lesch; Daniel C. Anthony; Lee Wei Lim (Psychopharmacology, 2022)
Rationale The chronic mild stress (CMS) paradigm was first described almost 40 years ago and has become a widely used model in the search for antidepressant drugs for major depression disorder (MDD). It has resulted in the publication of almost 1700 studies in rats alone. Under the original CMS procedure, the expression of an anhedonic response, a key symptom of depression, was seen as an essential feature of both the model and a depressive state. The prolonged exposure of rodents to unpredictable/uncontrollable mild stressors leads to a reduction in the intake of palatable liquids, behavioral despair, locomotor inhibition, anxiety-like changes, and vegetative (somatic) abnormalities. Many of the CMS studies do not report these patterns of behaviors, and they often fail to include consistent molecular, neuroanatomical, and physiological phenotypes of CMS-exposed animals. Objectives To critically review the CMS studies in rats so that conceptual and methodological flaws can be avoided in future studies. Results Analysis of the literature supports the validity of the CMS model and its impact on the field. However, further improvements could be achieved by (i) the stratification of animals into ‘resilient’ and ‘susceptible’ cohorts within the CMS animals, (ii) the use of more refined protocols in the sucrose test to mitigate physiological and physical artifacts, and (iii) the systematic evaluation of the non-specific effects of CMS and implementation of appropriate adjustments within the behavioral tests. Conclusions We propose methodological revisions and the use of more advanced behavioral tests to refine the rat CMS paradigm, which offers a valuable tool for developing new antidepressant medications.

The Synergistic Impacts of Anthropogenic Stressors and COVID-19 on Aquaculture: A Current Global Perspective - G. Sarà; M. C. Mangano; M. Berlino; L. Corbari; M. Lucchese; G. Milisenda; S. Terzo; M. S. Azaza; J. M. F. Babarro; R. Bakiu; B. R. Broitman; A. H. Buschmann; et al. (Reviews in Fisheries Science & Aquaculture, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Ice‐Ice disease: An environmentally and microbiologically driven syndrome in tropical seaweed aquaculture - Georgia M. Ward; Cicilia S. B. Kambey; Joseph P. Faisan; Pui‐Ling Tan; Caroline C. Daumich; Ivy Matoju; Grant D. Stentiford; David Bass; Phaik‐Eem Lim; Juliet Brodie; Sze‐Wan Poong (Reviews in Aquaculture, 2022)
Seaweeds account for nearly 30% of global aquaculture production by volume, and their cultivation provides important opportunities for employment and wealth generation, particularly in rural coastal communities. Eucheumatoids ( Kappaphycus and Eucheuma spp.) are tropical red algae commercially cultivated as raw material for production of carrageenans, particularly in South‐East Asia and the Western Indian Ocean region. Diseases and pests are major limiting factors in eucheumatoid production, particularly a condition known as ‘ice‐ice’ disease (IID). IID is characterized by bleaching of the thallus followed by the disintegration of affected tissues, leading to a loss of biomass and reduced carrageenan yield. IID has been associated with unfavourable changes in environmental conditions, particularly an increase in sea water temperature and a decrease in salinity, and infection by opportunistic or pathogenic bacteria. However, given that no single or combined causal agents have been definitely identified, IID may be considered a complex pathobiotic syndrome in which multiple factors contribute to the development of disease signs. Here, we review current knowledge of the abiotic and biotic factors associated with the development of IID, and the strategies employed to mitigate economic losses resulting from disease outbreaks. We discuss syndromic diseases in other marine holobionts, particularly other red algae and corals, in relation to their similarity to IID, and suggest the application of comprehensive and complementary methodologies, including high‐throughput sequencing and high‐quality microscopy, for enhancing our understanding of the pathological and microbiological processes associated with IID signs.

Photo-Fenton process for removal of polycyclic aromatic hydrocarbons from hazardous waste landfill leachate - P. K. Singa; M. H. Isa; J. -W. Lim; Y. -C. Ho; S. Krishnan (International Journal of Environmental Science and Technology, 2021)

Dietary Supplementation of Bacillus sp. SJ-10 and Lactobacillus plantarum KCCM 11322 Combinations Enhance Growth and Cellular and Humoral Immunity in Olive Flounder (Paralichthys olivaceus) - Md Tawheed Hasan; Won Je Jang; Bong-Joo Lee; Sang Woo Hur; Sang Gu Lim; Kang Woong Kim; Hyon-Sob Han; Eun-Woo Lee; Sungchul C Bai; In-Soo Kong (Probiotics and Antimicrobial Proteins, 2021)

Comparing the clinical outcomes across different sodium/glucose cotransporter 2 (SGLT2) inhibitors in heart failure patients: a systematic review and network meta-analysis of randomized controlled trials - Yao Hao Teo; Celine Shuen Yin Yoong; Nicholas L. Syn; Yao Neng Teo; Jia Yang Alex Cheong; Yoke-Ching Lim; Chi-Hang Lee; Tiong-Cheng Yeo; Ping Chai; Raymond C. C. Wong; Weiqin Lin; Ching-Hui Sia (European Journal of Clinical Pharmacology, 2021)

Natural seismic metamaterials: the role of tree branches in the birth of Rayleigh wave bandgap for ground born vibration attenuation - Muhammad; C. W. Lim (Trees, 2021)

Genetic structure and population history in two critically endangered Kaua‘i honeycreepers - Loren Cassin-Sackett; Michael G. Campana; Nancy Rotzel McInerney; Haw Chuan Lim; Natalia A. S. Przelomska; Bryce Masuda; R. Terry Chesser; Eben H. Paxton; Jeffrey T. Foster; Lisa H. Crampton; Robert C. Fleischer (Conservation Genetics, 2021)

An agenda for research and action toward diverse and just futures for life on Earth - C. Wyborn; J. Montana; N. Kalas; S. Clement; F. Davila; N. Knowles; E. Louder; M. Balan; J. Chambers; L. Christel; T. Forsyth; G. Henderson; et al. (Conservation Biology, 2021)
Decades of research and policy interventions on biodiversity have insufficiently addressed the dual issues of biodiversity degradation and social justice. New approaches are therefore needed. We devised a research and action agenda that calls for a collective task of revisiting biodiversity toward the goal of sustaining diverse and just futures for life on Earth. Revisiting biodiversity involves critically reflecting on past and present research, policy, and practice concerning biodiversity to inspire creative thinking about the future. The agenda was developed through a 2‐year dialogue process that involved close to 300 experts from diverse disciplines and locations. This process was informed by social science insights that show biodiversity research and action is underpinned by choices about how problems are conceptualized. Recognizing knowledge, action, and ethics as inseparable, we synthesized a set of principles that help navigate the task of revisiting biodiversity. The agenda articulates 4 thematic areas for future research. First, researchers need to revisit biodiversity narratives by challenging conceptualizations that exclude diversity and entrench the separation of humans, cultures, economies, and societies from nature. Second, researchers should focus on the relationships between the Anthropocene, biodiversity, and culture by considering humanity and biodiversity as tied together in specific contexts. Third, researchers should focus on nature and economies by better accounting for the interacting structures of economic and financial systems as core drivers of biodiversity loss. Finally, researchers should enable transformative biodiversity research and action by reconfiguring relationships between human and nonhuman communities in and through science, policy, and practice. Revisiting biodiversity necessitates a renewed focus on dialogue among biodiversity communities and beyond that critically reflects on the past to channel research and action toward fostering just and diverse futures for human and nonhuman life on Earth.

Lipopolysaccharide-Induced Exosomal miR-146a Is Involved in Altered Expression of Alzheimer’s Risk Genes Via Suppression of TLR4 Signaling - Junling Yang; Fiona Malone; Michelle Go; Jinghong Kou; Jeong-Eun Lim; Robert C. Caughey; Ken-ichiro Fukuchi (Journal of Molecular Neuroscience, 2021)

Exploring atmospheric circulation leading to three anomalous Australian spring heat events - Roseanna C. McKay; Julie M. Arblaster; Pandora Hope; Eun-Pa Lim (Climate Dynamics, 2021)

Examining privilege and power in US urban parks and open space during the double crises of antiblack racism and COVID-19 - Fushcia -Ann Hoover; Theodore C. Lim (Socio-Ecological Practice Research, 2021)

Toxicological and pharmacokinetic analysis at therapeutic dose of SRS27, an investigational anti-asthma agent - J. C. W. Lim; S. R. Sagineedu; A. C. H. Yong; S. M. Sidik; W. S. F. Wong; J. Stanslas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Impact of formulary interventions on the minimum inhibitory concentration of methicillin-resistant Staphylococcus aureus to mupirocin, chlorhexidine, and octenidine in a Singapore tertiary institution - Shuwei Zheng; S. J. Chung; H. C. J. Sim; T. M. Chlebicka; Y. H. Chan; T. P. Lim; L. H. A. Kwa; M. P. Chlebicki (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Elevated incubation temperature improves later‐life swimming endurance in juvenile Chinook salmon, Oncorhynchus tshawytscha - Dan Dohyung Lim; C. Louise Milligan; Yolanda E. Morbey (Journal of Fish Biology, 2020)
The effect of incubation and rearing temperature on muscle development and swimming endurance under a high‐intensity swimming test was investigated in juvenile Chinook salmon ( Oncorhynchus tshawytscha ) in a hatchery experiment. After controlling for the effects of fork length ( L F ) and parental identity, times to fatigue of fish were higher when fish were incubated or reared at warmer temperatures. Significant differences among combinations of pre‐ and post‐emergence temperatures conformed to 15–15°C > 15–9°C > 9–9°C > 7–9°C > 7–7°C in 2011 when swimming tests were conducted at 300 accumulated temperature units post‐emergence and 15–9°C > (7–9°C = 7–7°C) in 2012 when swimming tests were conducted at an L F of c. 40 mm. The combination of pre‐ and post‐emergence temperatures also affected the number and size of muscle fibres, with differences among temperature treatments in mean fibre cross‐sectional area persisting after controlling for L F and parental effects. Nonetheless, neither fibre number nor fibre size accounted for significant variation in swimming endurance. Thus, thermal carryover effects on swimming endurance were not mediated by thermal imprinting of muscle structure. This is the first study to test how temperature, body size and muscle structure interact to affect swimming endurance during early development in salmon.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Morphological and molecular evidence for the recognition of Hypoglossum sabahense sp. nov. (Delesseriaceae, Rhodophyta) from Sabah, Malaysia - Michael J. Wynne; Mitsunobu Kamiya; John A. West; Susan Loiseaux-de Goër; Phaik-Eem Lim; Ahemad Sade; Hannah Russell; Frithjof C. Küpper (Algae, 2020)

Whole-Genome Sequencing of Aspergillus terreus Species Complex - Mathangi Palanivel; Micheál Mac Aogáin; Rikky W. Purbojati; Akira Uchida; Ngu War Aung; Serene B. Y. Lim; Alexander Putra; Daniela I. Drautz-Moses; Shila Seaton; Thomas R. Rogers; Stephan C. Schuster; Sanjay H. Chotirmall (Mycopathologia, 2020)

A likely increase in fine particulate matter and premature mortality under future climate change - S. Park; R. J. Allen; C. H. Lim (Air Quality, Atmosphere & Health, 2020)
Climate change modulates the concentration of fine particulate matter (PM 2.5 ) via modifying atmospheric circulation, temperature, and the hydrological cycle. Furthermore, PM 2.5 is associated with cardiopulmonary diseases and premature mortality. Here, we use seven models to assess the response of PM 2.5 to end of the twenty-first century climate change under Representative Concentration Pathway 8.5, and the corresponding impact on premature mortality. The majority of models yield an increase in both PM 2.5 and premature mortality associated with lung cancer and cardiopulmonary disease in all world regions except Africa. These results are robust across five different future population projections, although the magnitude of premature deaths can vary by up to a factor of two. Much larger uncertainty is related to uncertainty in model physics and the representation of aerosol processes. Although our analysis requires several assumptions related to future population estimates, as well as the concentration-response function, results suggest that future emission reductions are necessary to avoid the likely health risks associated with increasing PM 2.5 in a warmer world.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Risk-stratified approach to anti-viral prophylaxis against cytomegalovirus disease in glomerulonephritis and renal vasculitis treated with potent immunosuppressants - Cynthia Ciwei Lim; Ban Hock Tan; Yu Tzu Tung; Huijun Huang; Ying Hao; Irene Y. J. Mok; Puay Hoon Lee; Jason C. J. Choo (Infectious Diseases, 2019)

Use of the McHargian LUSA in agricultural research and decision-making in the age of non-stationarity and big earth observation data - Theodore C Lim (Socio-Ecological Practice Research, 2019)

Mapping of the cystine–glutamate exchanger in the mouse eye: a role for xCT in controlling extracellular redox balance - Renita M. Martis; Paul J. Donaldson; Bo Li; Martin Middleditch; Prasanna K. Kallingappa; Julie C. Lim (Histochemistry and Cell Biology, 2019)

Dynamic Weakening of Sandstone Subjected to Repetitive Impact Loading - L. H. Tong; Yang Yu; S. K. Lai; C. W. Lim (Rock Mechanics and Rock Engineering, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Challenges in the Detection of Ionospheric Pre-Earthquake Total Electron Content Anomalies (PETA) for Earthquake Forewarning - B. J. M. Lim; E. C. Leong (Pure and Applied Geophysics, 2019)

A Blend of F Prostaglandins Functions as an Attractive Sex Pheromone in Silver Carp - Peter W. Sorensen; Mara C. P. Rue; Joseph M. Leese; Ratna Ghosal; Hangkyo Lim (Fishes, 2019)
A series of laboratory experiments tested the hypothesis that the Silver Carp (Hypophthalmichthys molitrix), an invasive river carp from China, employs a prostaglandin F2α-derived sex pheromone that is attractive and species-specific. Using electro-olfactogram recording (EOG), we found that the olfactory system of this species is acutely sensitive to three F-series prostaglandins (PGFs) at picomolar concentrations and that this sensitivity is enhanced when juveniles are masculinized using androgens, consistent with expectations of a sex pheromone. Individual PGFs had behavioral activity but it was low, suggesting a mixture might be important. To pursue this possibility, we implanted carps with osmotic pumps containing prostaglandin F2α (PGF2α), a treatment previously shown to elicit release of a PGF-based spawning pheromone in the Common Carp. We found that PGF2α-implanted Silver Carp released a species-specific odor that contained a blend of PGF2α and two of its metabolites, which masculinized individuals detected and were attracted to with high sensitivity. Finally, we found that a mixture of these PGFs was attractive to masculinized Silver Carp, while a different mixture released by Bighead Carp was not. We conclude that Silver Carp likely use a species-specific PGF2α-derived sex pheromone that is probably released at spawning and might be useful in its control. Confirmatory studies that explore pheromone function in naturally mature Silver Carp using natural odors in the field should now be conducted to further confirm our proof-of-concept study.

A new software scheme for scatter correction based on a simple radiographic scattering model - K. Kim; S. Kang; W. Kim; C. Park; D. Lee; H. Cho; W. Kang; S. Park; G. Kim; H. Lim; H. Lee; J. Park; et al. (Medical & Biological Engineering & Computing, 2019)

A comprehensive review on state-of-the-art photo-, sono-, and sonophotocatalytic treatments to degrade emerging contaminants - H. C. Yap; Y. L. Pang; S. Lim; A. Z. Abdullah; H. C. Ong; C.-H. Wu (International Journal of Environmental Science and Technology, 2019)

Effect of Coral-Algal Interactions on Early Life History Processes in Pocillopora acuta in a Highly Disturbed Coral Reef System - Rick C. Leong; Ezequiel M. Marzinelli; Jeffrey Low; Andrew G. Bauman; Elton W. X. Lim; Chin Y. Lim; Peter D. Steinberg; James R. Guest (Frontiers in Marine Science, 2018)

Effects of antiepileptic drugs on lipogenic gene regulation and hyperlipidemia risk in Taiwan: a nationwide population-based cohort study and supporting in vitro studies - Yi-Wen Li; Chung-Hsing Wang; Chao-Jung Chen; Charles C. N. Wang; Cheng-Li Lin; Wai-Kok Cheng; Hsin-Yi Shen; Yun-Ping Lim (Archives of Toxicology, 2018)

Bottom‐up influences on tropical freshwater food web structure support the “environmental filtering” hypothesis - J. H. Liew; T. D. Jardine; R. B. H. Lim; J. T. B. Kwik; H. H. Tan; Z. Y. Kho; D. C. J. Yeo (Limnology and Oceanography, 2018)
Studies of ecosystem functions are gaining traction in the scientific community along with a growing consensus that losses in ecosystem functions have widespread consequences. Food webs, which are networks comprising all trophic interactions (represented by links) between taxa present in a community (represented by nodes), are important aspects of ecosystem functioning, yet a clear understanding of the factors and mechanisms influencing their assembly and structure is lacking. In our study, we addressed this fundamental question by investigating the respective roles of (1) environmental filtering and (2) biotic filtering, in governing food web structure. We did this by assessing the relationship between the network structure of five high‐resolution empirical tropical food webs and associated environmental and biotic covariates. Our data suggest that only environmental filtering is important in shaping food webs. Further, we found that the underlying ecological mechanism is a function of bottom‐up influences comprising resource levels, and to a lesser degree, resource type (i.e., terrestrial organic matter) available. Specifically, our data suggest high‐nutrient environments favor greater food web complexity. In the general context of community assembly, our findings add to existing knowledge of the process by demonstrating that environmental conditions previously shown to influence species assemblages can also drive trends in prevailing species interactions.

Bioregeneration of granular activated carbon loaded with phenolic compounds: effects of biological and physico-chemical factors - P.-Y. Chan; P.-E. Lim; S.-L. Ng; C.-E. Seng (International Journal of Environmental Science and Technology, 2018)

Mytella strigata (Bivalvia: Mytilidae): an alien mussel recently introduced to Singapore and spreading rapidly - J. Y. Lim; T. S. Tay; C. S. Lim; S. S. C. Lee; S. L.-M. Teo; K. S. Tan (Molluscan Research, 2018)

Freedom from Tritrichomonas foetus infection in cattle in St. Kitts - Kimberly E. Coker; Joseph J. Lim; Rebecca L. Schleisman; Christopher Vosloo; Hilari M. French; Juan C. Samper; John J. Callanan; Robert O. Gilbert; Fortune Sithole; Chaoqun Yao; Aspinas Chapwanya (Tropical Animal Health and Production, 2018)

Converging and emerging threats to health security - C. Raina MacIntyre; Thomas Edward Engells; Matthew Scotch; David James Heslop; Abba B. Gumel; George Poste; Xin Chen; Wesley Herche; Kathleen Steinhöfel; Samsung Lim; Alex Broom (Environment Systems and Decisions, 2018)

Effect of intranasal esketamine on cognitive functioning in healthy participants: a randomized, double-blind, placebo-controlled study - Randall L. Morrison; Maggie Fedgchin; Jaskaran Singh; Joop Van Gerven; Rob Zuiker; Kyoung Soo Lim; Peter van der Ark; Ewa Wajs; Liwen Xi; Peter Zannikos; Wayne C. Drevets (Psychopharmacology, 2018)

Lentic and lotic assemblages of zooplankton in a tropical reservoir, and their association with water quality conditions - W. O. Wan Maznah; S. Intan; R. Sharifah; C. C. Lim (International Journal of Environmental Science and Technology, 2018)

Adsorption of brilliant green from aqueous solution by unmodified and chemically modified Tarap (Artocarpus odoratissimus) peel - M. K. Dahri; L. B. L. Lim; M. R. R. Kooh; C. M. Chan (International Journal of Environmental Science and Technology, 2017)

Transgenic Mice Overexpressing the Divalent Metal Transporter 1 Exhibit Iron Accumulation and Enhanced Parkin Expression in the Brain - Cheng-Wu Zhang; Yee Kit Tai; Bing-Han Chai; Katherine C. M. Chew; Eng-Tat Ang; Fai Tsang; Bryce W. Q. Tan; Eugenia T. E. Hong; Abu Bakar Ali Asad; Kai-Hsiang Chuang; Kah-Leong Lim; Tuck Wah Soong (NeuroMolecular Medicine, 2017)

A framework for assessing readiness for tiger Panthera tigris reintroduction: a case study from eastern Cambodia - T. N. E. Gray; R. Crouthers; K. Ramesh; J. Vattakaven; J. Borah; M. K. S. Pasha; T. Lim; C. Phan; R. Singh; B. Long; S. Chapman; O. Keo; et al. (Biodiversity and Conservation, 2017)

A balancing act in urban social-ecology: human appreciation, ponds and dragonflies - Robin Wen Jiang Ngiam; Wei Ling Lim; C. Matilda Collins (Urban Ecosystems, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Increased risk of chronic osteomyelitis after hip replacement: a retrospective population-based cohort study in an Asian population - D.-Z. Hung; N. Tien; C.-L. Lin; Y.-R. Lee; C. C. N. Wang; J.-J. Chen; Y.-P. Lim (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Impact of natural and calcined starfish (Asterina pectinifera) on the stabilization of Pb, Zn and As in contaminated agricultural soil - Jung Eun Lim; Jwa Kyung Sung; Binoy Sarkar; Hailong Wang; Yohey Hashimoto; Daniel C. W. Tsang; Yong Sik Ok (Environmental Geochemistry and Health, 2017)

Application of Adaptive Starling-Like Controller to Total Artificial Heart Using Dual Rotary Blood Pumps - Boon C. Ng; Peter A. Smith; Frank Nestler; Daniel Timms; William E. Cohn; Einly Lim (Annals of Biomedical Engineering, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Kynurenines, Gender and Neuroinflammation; Showcase Schizophrenia - J. de Bie; C. K. Lim; G. J. Guillemin (Neurotoxicity Research, 2016)

Osteogenic Treatment Initiating a Tissue-Engineered Cartilage Template Hypertrophic Transition - J. Y. Fu; S. Y. Lim; P. F. He; C. J. Fan; D. A. Wang (Annals of Biomedical Engineering, 2016)

Comparison of laboratory and field testing performance evaluations of siloxane-polyurethane fouling-release marine coatings - Shane J. Stafslien; Stacy Sommer; Dean C. Webster; Rajan Bodkhe; Robert Pieper; Justin Daniels; Lyndsi Vander Wal; Maureen C. Callow; James A. Callow; Emily Ralston; Geoff Swain; Lenora Brewer; et al. (Biofouling, 2016)

Altered neural activation during prepotent response inhibition in breast cancer survivors treated with chemotherapy: an fMRI study - Julia W. Y. Kam; Lara A. Boyd; Chun L. Hsu; Teresa Liu-Ambrose; Todd C. Handy; Howard J. Lim; Sherri Hayden; Kristin L. Campbell (Brain Imaging and Behavior, 2016)

Mu rhythm suppression demonstrates action representation in pianists during passive listening of piano melodies - C. Carolyn Wu; Jeff P. Hamm; Vanessa K. Lim; Ian J. Kirk (Experimental Brain Research, 2016)

Community assembly on isolated islands: macroecology meets evolution - A. J. Rominger; K. R. Goodman; J. Y. Lim; E. E. Armstrong; L. E. Becking; G. M Bennett; M. S. Brewer; D. D. Cotoras; C. P. Ewing; J. Harte; N. D. Martinez; P. M. O'Grady; et al. (Global Ecology and Biogeography, 2016)
Aim Understanding how ecological and evolutionary processes together determine patterns of biodiversity remains a central aim in biology. Guided by ecological theory, we use data from multiple arthropod lineages across the Hawaiian archipelago to explore the interplay between ecological (population dynamics, dispersal, trophic interactions) and evolutionary (genetic structuring, adaptation, speciation, extinction) processes. Our goal is to show how communities develop from the dynamic feedbacks that operate at different temporal and spatial scales. Location The Hawaiian islands (19–22° N , 155–160° W ). Methods We synthesize genetic data from selected arthropods across the Hawaiian archipelago to determine the relative role of dispersal and in situ differentiation across the island chronosequence. From four sites on three high islands with geological ages ranging from Results From the perspective of the island chronosequence we show that species at lower trophic levels develop population genetic structure at smaller temporal and spatial scales than species at higher trophic levels. Network nestedness decreases while modularity increases with habitat age. Single‐island endemics exhibit more specialization than broadly distributed species, but both show the least specialization in communities on middle‐aged substrates. Plant–herbivore networks also show the least deviation from theoretical predictions in middle‐aged communities. Main conclusions The application of ecological theory to island chronosequences can illuminate feedbacks between ecological and evolutionary processes in community assembly. We show how patterns of population genetic structure, decreasing network nestedness, increasing network modularity and increased specialization shift from early assembly driven by immigration, to in situ diversification after > 1 Myr. Herbivore–plant communities only transiently achieve statistical steady state during assembly, presumably due to incomplete assembly from dispersal in the early stages, and the increasing influence of island ontogeny on older islands.

Roles of nitrogen and phosphorus in growth responses and toxin production (using LC-MS/MS) of tropical Microcystis ichthyoblabe and M. flos-aquae - Maxine A. D. Mowe; Feras Abbas; Cristina Porojan; Simon M. Mitrovic; Richard P. Lim; Ambrose Furey; Darren C. J. Yeo (Journal of Applied Phycology, 2016)

Brain activation in response to overt and covert fear and happy faces in women with borderline personality disorder - Kathryn R. Cullen; Lori L. LaRiviere; Nathalie Vizueta; Kathleen M. Thomas; Ruskin H. Hunt; Michael J. Miller; Kelvin O. Lim; Sellman C. Schulz (Brain Imaging and Behavior, 2016)

Numerical Simulation of a Biventricular Assist Device with Fixed Right Outflow Cannula Banding During Pulmonary Hypertension - K. Nadeem; B. C. Ng; E. Lim; S. D. Gregory; R. F. Salamonsen; M. C. Stevens; M. Mubin; N. H. Lovell (Annals of Biomedical Engineering, 2016)

A statistical model to predict total column ozone in Peninsular Malaysia - K. C. Tan; H. S. Lim; M. Z. Mat Jafri (Frontiers of Earth Science, 2016)

In vivo Evaluation of Cenderitide-Eluting Stent (CES) II - Yingying Huang; Xu Wen Ng; Soon Ghim Lim; Horng Haur Chen; John C. Burnett; Yin Chiang Freddy Boey; Subbu S. Venkatraman (Annals of Biomedical Engineering, 2016)

Novel antibiotics regeneration and genetic transformation with RsMYB1 gene of recalcitrant chrysanthemum cv. Shinma - A. H. Naing; T. Ngoc Ai; S. M. Jeon; K. I. Park; S. H. Lim; K. B. Lim; C. K. Kim (Plant Biosystems, 2016)

Assessing patterns of admixture and ancestry in Canadian honey bees - B. A. Harpur; N. C. Chapman; L. Krimus; P. Maciukiewicz; V. Sandhu; K. Sood; J. Lim; T. E. Rinderer; M. H. Allsopp; B. P. Oldroyd; A. Zayed (Insectes Sociaux, 2015)

A potential bioconversion of empty fruit bunches into organic fertilizer using Eudrilus eugeniae - P. N. Lim; T. Y. Wu; C. Clarke; N. N. Nik Daud (International Journal of Environmental Science and Technology, 2015)

Quantification of gas emissions from stored softwood chips as solid biofuels - X. He; A. K. Lau; S. Sokhansanj; C. J. Lim; X. T. Bi; S. Melin (International Journal of Environmental Science and Technology, 2015)

Influences of diatom frustule morphologies on protein adsorption behavior - G. W. Lim; J. K. Lim; A. L. Ahmad; D. J. C. Chan (Journal of Applied Phycology, 2015)

A Head-to-Head Comparison of the Antimicrobial Activities of 30 Ultra-Short Antimicrobial Peptides Against Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans - Qiu Ying Lau; Xing Yao Choo; Zhi Xue Lim; Xin Ni Kong; Fui Mee Ng; Melgious J. Y. Ang; Jeffrey Hill; C. S. Brian Chia (International Journal of Peptide Research and Therapeutics, 2015)

Anti-tuberculosis treatments and risk of hepatocellular carcinoma in tuberculosis patients with liver cirrhosis: a population-based case–control study - Y.-P. Lim; C.-L. Lin; D.-Z. Hung; Y.-N. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Novel life‐history data for threatened seahorses provide insight into fishery effects - J. M. Lawson; S. J. Foster; A. C. O. Lim; V. C. Chong; A. C. J. Vincent (Journal of Fish Biology, 2015)
Life‐history variables for three incidentally captured species of seahorse (Kellogg's seahorse Hippocampus kelloggi , the hedgehog seahorse Hippocampus spinosissimus and the three‐spot seahorse Hippocampus trimaculatus ) were established using specimens obtained from 33 fisheries landing sites in Peninsular Malaysia. When samples were pooled by species across the peninsula, sex ratios were not significantly different from unity, and height and mass relationships were significant for all species. For two of these species, height at physical maturity ( H M ) was smaller than the height at which reproductive activity ( H R ) commenced: H. spinosissimus ( H M = 99·6 mm, H R = 123·2 mm) and H. trimaculatus ( H M = 90·5 mm, H R = 121·8 mm). For H. kelloggi , H M could not be estimated as all individuals were physically mature, while H R = 167·4 mm. It appears that all three Hippocampus spp. were, on average, caught before reproducing; height at 50% capture ( H C ) was ≥ H M but ≤ H R . The results from this study probe the effectiveness of assessment techniques for data‐poor fisheries that rely heavily on estimates of length at maturity, especially if maturity is poorly defined. Findings also question the sustainability of H. trimaculatus catches in the south‐west region of Peninsular Malaysia, where landed specimens had a notably smaller mean height (86·2 mm) and markedly skewed sex ratio (6% males) compared with samples from the south‐east and north‐west of the peninsula.

Albumin and glycated albumin activate KIM-1 release in tubular epithelial cells through distinct kinetics and mechanisms - Ai Ing Lim; Loretta Y. Y. Chan; Sydney C. W. Tang; Kar Neng Lai; Joseph C. K. Leung (Inflammation Research, 2014)

Multiple regression analysis in modeling of columnar ozone in Peninsular Malaysia - K. C. Tan; H. S. Lim; M. Z. Mat Jafri (Environmental Science and Pollution Research, 2014)

Capsule endoscopy versus magnetic resonance enterography for the detection of small bowel polyps in Peutz–Jeghers syndrome - P. Urquhart; F. Grimpen; G. J. Lim; C. Pizzey; D. L. Stella; P. A. Tesar; F. A. Macrae; M. A. Appleyard; G. J. Brown (Familial Cancer, 2014)

Cognitive Ability and Cardiovascular Control in Intellectually and Developmentally Disabled People - H. S. Kim; M. H. Choi; I. H. Lee; S. P. Hong; N. R. You; H. J. Kim; D. W. Lim; S. C. Chung (Neurophysiology, 2014)

Manipulating visual–motor experience to probe for observation-induced after-effects in adaptation learning - Shannon B. Lim; Beverley C. Larssen; Nicola J. Hodges (Experimental Brain Research, 2014)

Accuracy assessment of a mobile terrestrial lidar survey at Padre Island National Seashore - Samsung Lim; Cindy A. Thatcher; John C. Brock; Dustin R. Kimbrow; Jeffrey J. Danielson; B.J. Reynolds (International Journal of Remote Sensing, 2013)

The MCIC Collection: A Shared Repository of Multi-Modal, Multi-Site Brain Image Data from a Clinical Investigation of Schizophrenia - Randy L. Gollub; Jody M. Shoemaker; Margaret D. King; Tonya White; Stefan Ehrlich; Scott R. Sponheim; Vincent P. Clark; Jessica A. Turner; Bryon A. Mueller; Vince Magnotta; Daniel O’Leary; Beng C. Ho; et al. (Neuroinformatics, 2013)

Analysis of the association between air pollution and allergic diseases exposure from nearby sources of ambient air pollution within elementary school zones in four Korean cities - H.-H. Kim; C.-S. Lee; J.-M. Jeon; S.-D. Yu; C.-W. Lee; J.-H. Park; D.-C. Shin; Y.-W. Lim (Environmental Science and Pollution Research, 2013)

Molecular identification and cellular localisation of GSH synthesis, uptake, efflux and degradation pathways in the rat ciliary body - Bo Li; Ankita Umapathy; Loi Uyen Tran; Paul J. Donaldson; Julie C. Lim (Histochemistry and Cell Biology, 2013)

Assessing the Chronic Toxicity of Atrazine, Permethrin, and Chlorothalonil to the Cladoceran Ceriodaphnia cf. dubia in Laboratory and Natural River Water - Yin Latt Phyu; C. G. Palmer; M. St. J. Warne; R. Dowse; S. Mueller; J. Chapman; G. C. Hose; R. P. Lim (Archives of Environmental Contamination and Toxicology, 2013)

Exploring Solution-Phase Cyclization and Sulfamyl Safety-Catch Resin Strategies for the Total Synthesis of the Marine Antimicrobial Cyclic Tetrapeptide Cyclo(GSPE) - Huichang A. Lim; Lik Tong Tan; C. S. Brian Chia (International Journal of Peptide Research and Therapeutics, 2013)

High intra-individual sequence variation in the nuclear rDNA LSU-5S intergenic spacer in the Sargassaceae (Fucales, Phaeophyceae) - Stefano G. A. Draisma; Marcel C. M. Eurlings; Phaik-Eem Lim (Journal of Applied Phycology, 2012)

Phenotypic and genetic characterization of Erwinia rhapontici isolated from diseased Asian pear fruit trees - S. P. Thapa; S. Y. Cho; J. H. Hur; C. K. Lim (Phytoparasitica, 2012)

Utility and safety of procalcitonin in an antimicrobial stewardship program (ASP) in patients with malignancies - Y. X. Liew; W. Lee; Y. Y. Cai; J. Teo; S. S.-L. Tang; R. W.-Q. Ong; C. L.-L. Lim; P. B. Lingegowda; A. L.-H. Kwa; M. P. Chlebicki (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Quantitative PCR and in vivo efficacy of antibiotics in the treatment of Vibrio vulnificus infection in a mouse model - G. P. Neupane; D.-M. Kim; N. R. Yun; S.-H. Shin; S.-C. Lim; C.-H. Choi (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Clinical significance of enzymatic lysophosphatidylcholine (LPC) assay data in patients with sepsis - W. H. Cho; T. Park; Y. Y. Park; J. W. Huh; C.-M. Lim; Y. Koh; D.-K. Song; S.-B. Hong (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

QTLs for murine red blood cell parameters in LG/J and SM/J F2 and advanced intercross lines - Thomas B. Bartnikas; Clarissa C. Parker; Riyan Cheng; Dean R. Campagna; Jackie E. Lim; Abraham A. Palmer; Mark D. Fleming (Mammalian Genome, 2012)

Racial mixing in South African honeybees: the effects of genotype mixing on reproductive traits of workers - Madeleine Beekman; Michael H. Allsopp; Michael J. Holmes; Julianne Lim; Lee-Ann Noach-Pienaar; Theresa C. Wossler; Benjamin P. Oldroyd (Behavioral Ecology and Sociobiology, 2012)

Polymorphisms of the 5′ regulatory region of the porcine PPARGC1A gene and the effects on muscle fiber characteristics and meat quality - J. M. Kim; K. S. Lim; E. A. Lee; K. T. Lee; T. H. Kim; Y. C. Ryu; K. C. Hong (Molecular Biology Reports, 2012)

Prospective audit and feedback on antibiotic prescription in an adult hematology-oncology unit in Singapore - C.-L. Yeo; D. S.-G. Chan; A. Earnest; T.-S. Wu; S.-F. Yeoh; R. Lim; R. Jureen; D. Fisher; L.-Y. Hsu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

The IgE gene in primates exhibits extraordinary evolutionary diversity - Pheidias C. Wu; Jiun-Bo Chen; Shoji Kawamura; Christian Roos; Stefan Merker; Chih-Chin Shih; Ban-Dar Hsu; Carmay Lim; Tse Wen Chang (Immunogenetics, 2012)

Candida and invasive candidiasis: back to basics - C. S.-Y. Lim; R. Rosli; H. F. Seow; P. P. Chong (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

The role of black carbon as a catalyst for environmental redox transformation - Seok-Young Oh; Jong-Gil Son; Ock-Taeck Lim; Pei C. Chiu (Environmental Geochemistry and Health, 2012)

Identification of mediator complex 26 (Crsp7) gametologs on platypus X1 and Y5 sex chromosomes: a candidate testis-determining gene in monotremes? - Enkhjargal Tsend-Ayush; R. Daniel Kortschak; Pascal Bernard; Shu Ly Lim; Janelle Ryan; Ruben Rosenkranz; Tatiana Borodina; Juliane C. Dohm; Heinz Himmelbauer; Vincent R. Harley; Frank Grützner (Chromosome Research, 2012)

Vascular Wall Engineering Via Femtosecond Laser Ablation: Scaffolds with Self-Containing Smooth Muscle Cell Populations - Carol H. Lee; Yong C. Lim; Dave F. Farson; Heather M. Powell; John J. Lannutti (Annals of Biomedical Engineering, 2011)

Fine-mapping alleles for body weight in LG/J × SM/J F2 and F34 advanced intercross lines - Clarissa C. Parker; Riyan Cheng; Greta Sokoloff; Jackie E. Lim; Andrew D. Skol; Mark Abney; Abraham A. Palmer (Mammalian Genome, 2011)

High-resolution subtropical summer precipitation derived from dynamical downscaling of the NCEP/DOE reanalysis: how much small-scale information is added by a regional model? - Young-Kwon Lim; Lydia B. Stefanova; Steven C. Chan; Siegfried D. Schubert; James J. O’Brien (Climate Dynamics, 2011)

Anti-inflammatory/Anti-oxidative Stress Activities and Differential Regulation of Nrf2-Mediated Genes by Non-Polar Fractions of Tea Chrysanthemum zawadskii and Licorice Glycyrrhiza uralensis - Tien-Yuan Wu; Tin Oo Khor; Constance Lay Lay Saw; Stephanie C. Loh; Alvin I. Chen; Soon Sung Lim; Jung Han Yoon Park; Li Cai; Ah-Ng Tony Kong (The AAPS Journal, 2011)

Mapping QTL for an Adaptive Trait: The Length of Caudal Fin in Lates calcarifer - C. M. Wang; L. C. Lo; Z. Y. Zhu; H. Y. Pang; H. M. Liu; J. Tan; H. S. Lim; R. Chou; L. Orban; G. H. Yue (Marine Biotechnology, 2011)

Benthic macroinvertebrate assemblages in remediated wetlands around Sydney, Australia - Christopher A. Rawson; Richard P. Lim; Louis A. Tremblay; Michael St. J. Warne; Guang-guo Ying; Edwina Laginestra; John C. Chapman (Ecotoxicology, 2010)

Influence of fouling on the efficiency of sacrificial anodes in providing cathodic protection in Southeast Asian tropical seawater - D. J. Blackwood; C. S. Lim; S. L.M. Teo (Biofouling, 2010)

The complete genome sequence of freesia mosaic virus and its relationship to other potyviruses - H. I. Choi; H. R. Lim; Y. S. Song; M. J. Kim; S. H. Choi; Y. S. Song; S. C. Bae; K. H. Ryu (Archives of Virology, 2010)

Maternity of emergency queens in the Cape honey bee, Apis mellifera capensis - MICHAEL J. HOLMES; BENJAMIN P. OLDROYD; MICHAEL H. ALLSOPP; JULIANNE LIM; THERESA C. WOSSLER; MADELEINE BEEKMAN (Molecular Ecology, 2010)
During reproductive swarming, some workers of the Cape honey bee, Apis mellifera capensis , lay eggs in queen cells, many of which are reared to maturity. However, it is unknown if workers are able to lay in queen cells immediately after queen loss during an episode of emergency queen rearing. In this study we experimentally de‐queened colonies and determined the maternity of larvae and pupae that were reared as queens. This allowed us to determine how soon after queen loss workers contribute to the production of new queens. We were further interested to see if workers would preferentially raise new queens from queen‐laid brood if this was introduced later. We performed our manipulations in two different settings: an apiary setting where colonies were situated close together and a more natural situation in which the colonies were well separated. This allowed us to determine how the vicinity of other colonies affects the presence of parasites. We found that workers do indeed contribute to queen cell production immediately after the loss of their queen, thus demonstrating that some workers either have activated ovaries even when their colony has a queen or are able to activate their ovaries extremely rapidly. Queen‐laid brood introduced days after queen loss was ignored, showing that workers do not prefer to raise new queens from queen brood when given a choice. We also detected non‐natal parasitism of queen cells in both settings. We therefore conclude that some A. m. capensis genotypes specialize in parasitizing queen cells.

Elucidating the role of requiem in the growth and death of Chinese hamster ovary cells - Yiping Lim; Valerie X. F. Seah; Athanasios Mantalaris; Miranda G. S. Yap; Danny C. F. Wong (Apoptosis, 2010)

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations - Eng-King Tan; Chin-Hslen Lin; Chun-Hwei Tai; Louis C. Tan; Meng-Ling Chen; R. Li; Hui-Qin Lim; Ratnagopal Pavanni; Yih Yuen; K. M. Prakash; Yi Zhao; Ruey-Meei Wu (Human Genetics, 2009)

Differential membrane redistribution of P2X receptor isoforms in response to osmotic and hyperglycemic stress in the rat lens - Haruna Suzuki-Kerr; Julie C. Lim; Srdjan M. Vlajkovic; Paul J. Donaldson (Histochemistry and Cell Biology, 2009)

Phylogeography of the magpie‐robin species complex (Aves: Turdidae: Copsychus ) reveals a Philippine species, an interesting isolating barrier and unusual dispersal patterns in the Indian Ocean and Southeast Asia - Frederick H. Sheldon; David J. Lohman; Haw C. Lim; Fasheng Zou; Steven M. Goodman; Dewi M. Prawiradilaga; Kevin Winker; Thomas M. Braile; Robert G. Moyle (Journal of Biogeography, 2009)
Aim The oriental magpie‐robin ( Copsychus saularis ) of South and Southeast Asia is a phenotypically variable species that appears to be closely related to two endemic species of the western Indian Ocean: the Madagascar magpie‐robin ( Copsychus albospecularis ) and the Seychelles magpie‐robin ( Copsychus sechellarum ). This unusual distribution led us to examine evolutionary relationships in magpie‐robins, and also the taxonomic significance of their plumage variation, via a molecular phylogenetic and population genetic analysis of C. saularis and C. albospecularis . Location Southern Asia from Nepal across Indochina to southern China, and the Indian Ocean from Madagascar to the Greater Sunda and Philippine islands. Methods We sequenced 1695 nucleotides of mitochondrial DNA comprising the complete second subunit of the nicotinamide adenine dinucleotide dehydrogenase (ND2) gene and 654 bases of the cytochrome c oxidase subunit I (COI) region in 51 individuals of eight C. saularis subspecies, 10 individuals of C. albospecularis (one subspecies) and single individuals of two other Copsychus species as outgroups. The data were analysed phylogenetically, with maximum likelihood, Bayesian, relaxed clock and parsimony methods, and geographically for patterns of genetic diversity. Results Phylogenetic analysis indicated that C. albospecularis lies within the nominal C. saularis , making C. saularis polyphyletic. Malagasy and non‐Philippine Asian populations form a monophyletic group that is sister to a clade of Philippine populations. Within non‐Philippine Asian populations, two groups are evident: black‐bellied birds in the eastern Greater Sunda islands and white‐bellied birds in the western Sundas and on mainland Asia. Main conclusions The phylogeny of magpie‐robins suggests a novel pattern of dispersal and differentiation in the Old World. Ancestral magpie‐robins appear to have spread widely among islands of the Indian Ocean in the Pliocene, probably aided by their affinity for coastal habitats. Populations subsequently became isolated in island groups, notably the Philippines, Madagascar and the Greater Sundas, leading to speciation in all three areas. Isolation in the Philippines may have been aided by competitive exclusion of C. saularis from Palawan by a congener, the white‐vented shama ( Copsychus niger ). In the Greater Sundas, white‐bellied populations appear to have invaded Borneo and Java recently, where they hybridize with resident black‐bellied birds.

Effects of River Water and Salinity on the Toxicity of Deltamethrin to Freshwater Shrimp, Cladoceran, and Fish - Colette R. Thomas; Grant C. Hose; Michael StJ. Warne; Richard P. Lim (Archives of Environmental Contamination and Toxicology, 2008)

LRRK2 R1628P increases risk of Parkinson’s disease: replication evidence - E. K. Tan; Louis C. Tan; H. Q. Lim; R. Li; M. Tang; Yuen Yih; R. Pavanni; K. M. Prakash; S. Fook-Chong; Yi Zhao (Human Genetics, 2008)

Identification of random amplified polymorphic DNA (RAPD) marker for differentiating male from female and sporophytic thalli of Gracilaria changii (Rhodophyta) - M. C. Sim; P. E. Lim; S. Y. Gan; S. M. Phang (Journal of Applied Phycology, 2007)

Hydrostratigraphy and geochemistry at a coastal sandfill in Singapore - Lloyd H. C. Chua; Edmond Y. M. Lo; David L. Freyberg; E. B. Shuy; T. T. Lim; S. K. Tan; Mzila Ngonidzashe (Hydrogeology Journal, 2007)

Molecular identification of coxsackievirus A24 variant, isolated from an outbreak of acute hemorrhagic conjunctivitis in Singapore in 2005 - D. S.-Y. Yeo; S. G.-K. Seah; J. S.-W. Chew; E. A.-S. Lim; J. C.-W. Liaw; J.-P. Loh; B.-H. Tan (Archives of Virology, 2007)

The reference genetic linkage map for the multinational Brassica rapa genome sequencing project - Su Ryun Choi; Graham R. Teakle; Prikshit Plaha; Jeong Hee Kim; Charlotte J. Allender; Elena Beynon; Zhong Yun Piao; Pilar Soengas; Tae Ho Han; Graham J. King; Guy C. Barker; Paul Hand; et al. (Theoretical and Applied Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Water Quality Changes in Chini Lake, Pahang, West Malaysia - Mohammad Shuhaimi-Othman; Eng C. Lim; Idris Mushrifah (Environmental Monitoring and Assessment, 2007)

Perception of Conspecific Female Pheromone Stimulates Female Calling in an Arctiid Moth, Utetheisa ornatrix - Hangkyo Lim; Kye Chung Park; Thomas C. Baker; Michael D. Greenfield (Journal of Chemical Ecology, 2007)

Suppression of Endogenous Antioxidant Enzymes by 2,3,7,8-Tetrachlorodibenzo-p-dioxin–Induced Oxidative Stress in Chicken Liver During Development - J. Lim; J. C. DeWitt; R. A. Sanders; J. B. Watkins; D. S. Henshel (Archives of Environmental Contamination and Toxicology, 2007)

Social parasitism by workers in queenless and queenright Apis cerana colonies - P. NANORK; N. C. CHAPMAN; S. WONGSIRI; J. LIM; R. S. GLOAG; B. P. OLDROYD (Molecular Ecology, 2007)
We examined worker reproduction in queenless and queenright Apis cerana colonies to determine if they are parasitized by workers from other nests. The results demonstrate that 2–6% of workers in queenright colonies are from another nest (non‐natal), but these workers are not statistically more likely to have activated ovaries than natal workers, and are therefore unlikely to be active parasites. However, in queenless colonies we found a significant difference between the proportion of non‐natal (72.7%) and natal (36.3%) workers with activated ovaries. Non‐natal workers also had significantly higher reproductive success than natal workers: 1.8% of workers were non‐natal, but these laid 5.2% of the eggs and produced 5.5% of the pupae. Unlike A. florea , the proportion of non‐natal workers does not increase in queenless nests.

Cloning, Expression, and Characterization of a Methionyl Aminopeptidase from a Hyperthermophilic Archaeon Thermococcus sp. NA1 - H. S. Lee; Y. J. Kim; S. S. Bae; J. H. Jeon; J. K. Lim; B. C. Jeong; S. G. Kang; J.-H. Lee (Marine Biotechnology, 2006)

Inophyllin A, a new pyranoxanthone from Calophyllum inophyllum (Guttiferae) - G. C. L. Ee; A. S. M. Kua; C. K. Lim; V. Jong; H. L. Lee (Natural Product Research, 2006)

N-acetylphytosphingosine-induced apoptosis of Jurkat cells is mediated by the conformational change in Bak - Y. Han; Y. Kim; H. Kang; S. H. Hong; Y. H. Kim; D. -S. Lim; C. Park; Y. -S. Yun; J. -Y. Song (Apoptosis, 2006)

Physical mapping and microsynteny of Brassica rapa ssp. pekinensis genome corresponding to a 222 kbp gene-rich region of Arabidopsis chromosome 4 and partially duplicated on chromosome 5 - J. Y. Park; D. H. Koo; C. P. Hong; S. J. Lee; J. W. Jeon; S. H. Lee; P. Y. Yun; B. S. Park; H. R. Kim; J. W. Bang; P. Plaha; I. Bancroft; et al. (Molecular Genetics and Genomics, 2005)

An Integrated Modeling Approach to Total Watershed Management: Water Quality and Watershed Assessment of Cheney Reservoir, Kansas, USA - Steven H. Wang; Donald G. Huggins; Lyle Frees; Chad G. Volkman; Niang C. Lim; Debra S. Baker; Val Smith; Frank deNoyelles (Water, Air, & Soil Pollution, 2005)

The mycological and molecular study of Hortaea werneckii isolated from blood and splenic abscess - K. P. Ng; T. S. Soo-Hoo; S. L. Na; S. T. Tay; H. Hamimah; P. C. Lim; P. P. Chong; H. F. Seow; A. J. Chavez; S. A. Messer (Mycopathologia, 2005)

Neurophysiological examination of the corticospinal system and voluntary motor control in motor-incomplete human spinal cord injury - W. B. McKay; D. C. Lee; H. K. Lim; S. A. Holmes; A. M. Sherwood (Experimental Brain Research, 2005)

The Development of Marine Toxicity Identification Evaluation (TIE) Procedures Using the Unicellular Alga Nitzschia closterium - A. C. Hogan; J. L. Stauber; F. Pablo; M. S. Adams; R. P. Lim (Archives of Environmental Contamination and Toxicology, 2005)

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients - I.-J. Kim; J.-L. Ku; H. C. Kang; J.-H. Park; K.-A. Yoon; Y. Shin; H.-W. Park; S. G. Jang; S.-K. Lim; S. Y. Han; Y.-K. Shin; M. R. Lee; et al. (Human Genetics, 2004)

Use of 2n gametes for the production of sexual polyploids from sterile Oriental × Asiatic hybrids of lilies (Lilium) - R. Barba-Gonzalez; A. C. Lokker; K.-B. Lim; M. S. Ramanna; J. M. Van Tuyl (Theoretical and Applied Genetics, 2004)

Construction of a BAC library of Korean ginseng and initial analysis of BAC-end sequences - C. P. Hong; S. J. Lee; J. Y. Park; P. Plaha; Y. S. Park; Y. K. Lee; J. E. Choi; K. Y. Kim; J. H. Lee; J. Lee; H. Jin; S. R. Choi; et al. (Molecular Genetics and Genomics, 2004)

Classification of cardiac abnormalities using heart rate signals - R. Acharya; A. Kumar; P. S. Bhat; C. M. Lim; S. S. lyengar; N. Kannathal; S. M. Krishnan (Medical & Biological Engineering & Computing, 2004)

Feed deprivation of channel catfish, Ictalurus punctatus (Rafinesque), influences organosomatic indices, chemical composition and susceptibility to Flavobacterium columnare - C A Shoemaker; P H Klesius; C Lim; M Yildirim (Journal of Fish Diseases, 2003)
Withholding feed has been suggested as a strategy to manage infectious disease of channel catfish, Ictalurus punctatus (Rafinesque). In a previous study, we demonstrated that deprivation of feed for as little as 7 days reduced innate resistance of catfish to Flavobacterium columnare . This study was conducted to evaluate the effect of feeding regimens [no feeding (NF), fed once every other day to satiation (FEOD) and fed once daily to satiation (FD)] on organosomatic indices, physiological changes and susceptibility of channel catfish to F. columnare . Fish that were not fed for 2 and 4 weeks had a significant increase ( P −1 ) was significantly lower than that of the FD fish (41.77 mg mL −1 ). Significantly lower ( P −1 ) and liver glycogen (1.7 and 1.8 mg g −1 ) were seen in the NF fish at weeks 2 and 4, respectively, as compared with blood glucose and liver glycogen levels of FD fish (67.5 and 92.8 mg dL −1 and 46.5 and 52.6 mg g −1 at weeks 2 and 4, respectively) and FEOD (82.8 and 85.5 mg dL −1 and 45.1 and 51.4 mg g −1 at weeks 2 and 4, respectively). Mortality in the NF fish caused by F. columnare (78%) was significantly higher ( P −1 and 2 mg g −1 , respectively, are indicative of starvation in juvenile channel catfish. Moreover, NF fish were susceptible to F. columnare infection. Thus, it is suggested that in the absence of natural food, juvenile channel catfish should be fed at least once every other day to apparent satiation to maintain normal physiological function and improve resistance to F. columnare .

Platelet Aggregation Inhibitors from Philippine Marine Invertebrate Samples Screened in a New Microplate Assay - Sheila Marie V. Pimentel; Zenaida P. Bojo; Amy V. D. Roberto; Jose Enrico H. Lazaro; Gina C. Mangalindan; Leila M. Florentino; Pilar Lim-Navarro; Deniz Tasdemir; Chris M. Ireland; Gisela P. Concepcion (Marine Biotechnology, 2003)

Assessment of Metal Toxicity in Sediment Pore Water from Lake Macquarie, Australia - C. J. Doyle; F. Pablo; R. P. Lim; R. V. Hyne (Archives of Environmental Contamination and Toxicology, 2003)

Genetic variability in the coat protein genes of two orchid viruses: Cymbidium mosaic virus and Odontoglossum ringspot virus - P. A. Ajjikuttira; C. L. Lim-Ho; M. H. Woon; K. H. Ryu; C. A. Chang; C. S. Loh; S. M. Wong (Archives of Virology, 2002)

Aerobic reduction of manganese oxide by Salmonella sp. strain MR4 - K.-R. Pak; O.-Y. Lim; H.-K. Lee; S.-C. Choi (Biotechnology Letters, 2002)

A genetic analysis of the cytological region 46C-F containing the Drosophila melanogaster homolog of the jun proto-oncogene - E. Goldstein; S. Treadway; A. Stephenson; G. Gramstad; A. Keilty; L. Kirsch; M. Imperial; S. Guest; S. Hudson; A. LaBell; M. O'Day; C. Duncan; et al. (Molecular Genetics and Genomics, 2001)

Light- and electron-microscopic analysis of neuropeptide Y-immunoreactive amacrine cells in the guinea pig retina - Wha-Sun Kang; Min-Young Lim; Eun-Jin Lee; In-Beom Kim; Su-Ja Oh; Nicholas C. Brecha; Cheol-Beom Park; Myung-Hoon Chun (Cell and Tissue Research, 2001)

The sleeper Bostrichthys sinensis (Family Eleotridae) stores glutamine and reduces ammonia production during aerial exposure - Ip Y.; Chew S.; Leong I.; Jin Y.; Lim C.; Wu R. (Journal of Comparative Physiology B, 2001)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Comparative analysis of DNA methylation in tobacco heterochromatic sequences - A. Kovařík; B. Koukalová; K. Y. Lim; R. Matyášek; C. P. Lichtenstein; A. R. Leitch; M. Bezděk (Chromosome Research, 2000)

Effects of Selective Logging on the Butterflies of a Bornean Rainforest - S. J. Willott; D. C. Lim; S. G. Compton; S. L. Sutton (Conservation Biology, 2000)
Selective logging has been the main cause of disturbance to tropical forests in Southeast Asia, so the extent to which biodiversity is maintained in selectively logged forest is of prime conservation importance. We compared the butterfly assemblages of Bornean primary rainforest to those of rainforest selectively logged 6 years previously. We sampled by means of replicated transects stratified into riverine and ridge forests and we included roads in the logged forest. There was a three‐fold variation in species richness and abundance over the 8‐month sampling period. More species and individuals were observed in the logged forest, although between‐replicate variability was high. Rarefied species richness was positively correlated with canopy openness within the range of disturbance levels encountered at our forest sites. Within families, there was no significant difference in the number of species between primary and logged forest. There was a significant difference in the relative abundance of species, but this was due largely to the abundance of one or two species. Community ordination separated the sites along a gradient of disturbance and revealed strong differences between riverine and ridge‐forest butterfly assemblages in primary forest that were obscured in logged forest. There was no evidence that logging has resulted in a change in the composition of the butterfly assemblages from species with a local distribution to more widespread species. We conclude that at a logged forest site in close proximity to primary forest, low intensities of logging do not necessarily reduce the species richness or abundance of butterflies, although assemblage composition is changed.

Genetic analysis of freezing tolerance in blueberry (Vaccinium section Cyanococcus) - R. Arora; L. J. Rowland; J. S. Lehmann; C. C. Lim; G. R. Panta; N. Vorsa (Theoretical and Applied Genetics, 2000)

The genetics of rust resistance in sugar cane seedling populations - K. Ramdoyal; S. Sullivan; L. C. Y. Lim Shin Chong; G. H. Badaloo; S. Saumtally; R. Domaingue (Theoretical and Applied Genetics, 2000)

A 25-kDa dehydrin associated with genotype- and age-dependent leaf freezing-tolerance in Rhododendron: a genetic marker for cold hardiness? - C. C. Lim; S. L. Krebs; R. Arora (Theoretical and Applied Genetics, 1999)

The reach-to-grasp movement in Parkinson's disease: response to a simultaneous perturbation of object position and object size - U. Castiello; K. Bennett; C. Bonfiglioli; S. Lim; R. F. Peppard (Experimental Brain Research, 1999)

Flavonoid variation of theAconitum jaluense complex (Ranunculaceae) in Korea - C. E. Lim; J. H. Park; C. -W. Park (Plant Systematics and Evolution, 1999)

Growth activation of the microalga Isochrysis galbana by the aqueous extract of the seaweed Monostroma nitidum - Ji Young Cho; Hyung-Joo Jin; Hyun Jeong Lim; John N. C. Whyte; Yong-Ki Hong (Journal of Applied Phycology, 1998)

The distribution and frequency of microsatellite loci in Drosophila melanogaster - M. D. SCHUG; K. A. WETTERSTRAND; M. S. GAUDETTE; R. H. LIM; C. M. HUTTER; C. F. AQUADRO (Molecular Ecology, 1998)
We report the results of a comprehensive search of Drosophila melanogaster DNA sequences in GenBank for di‐, tri‐, and tetranucleotide repeats of more than four repeat units, and a DNA library screen for dinucleotide repeats. Dinucleotide repeats are more abundant (66%) than tri‐ (30%) or tetranucleotide (4%) repeats. We estimate that 1917 dinucleotide repeats with 10 or more repeat units are present in the euchromatic D. melanogaster genome and, on average, they occur once every 60 kb. Relative to many other animals, dinucleotide repeats in D. melanogaster are short. Tri‐ and tetranucleotide repeats have even fewer repeat units on average than dinucleotide repeats. Our WorldWide Web site (http://www.bio.cornell.edu/genetics/aquadro/aquadro.html) posts the complete list of 1298 microsatellites (≥ five repeat units) identified from the GenBank search. We also summarize assay conditions for 70 D. melanogaster microsatellites characterized in previous studies and an additional 56 newly characterized markers.

Effects of salinity, dietary level of protein and 17α-methyltestosterone on growth hormone (GH) and prolactin (tPRL177 and tPRL188) levels in the tilapia, Oreochromis mossambicus - B.S. Shepherd; B. Ron; A. Burch; R. Sparks; N.H. Richman; S.K. Shimoda; M.H. Stetson; C. Lim; E.G. Grau (Fish Physiology and Biochemistry, 1997)

Computerised prostate boundary estimation of ultrasound images using radial bas-relief method - Y. J. Liu; W. S. Ng; M. Y. Teo; H. C. Lim (Medical & Biological Engineering & Computing, 1997)

Steady flow velocity field and turbulent stress mappings downstream of a porcine bioprosthetic aortic valveIn Vitro - Wai L. Lim; Yong T. Chew; Tuan C. Chew; Hong T. Low (Annals of Biomedical Engineering, 1997)

An appraisal of the banded and paracrystalline cytoplasmic inclusions induced in cymbidium mosaic potexvirus- and odontoglossum ringspot tobamovirus infected orchid cells using confocal laser scanning microscopy - S. -M. Wong; C. G. Chng; Y. H. Lee; T. M. Lim (Archives of Virology, 1996)

Particle image velocimetry in the investigation of flow past artificial heart valves - W. L. Lim; Y. T. Chew; T. C. Chew; H. T. Low (Annals of Biomedical Engineering, 1994)